从「译文」到「世界文学」：以1950年代中国大陆的政治语境为例 = From Yi Wen to Shijie Wenxue : the politics in translation in the People's Republic of China in the 1950s - 崔峰 Cui Feng (2021)
《譯文》（《世界文學》）是一份由「中國作家協會」主辦的國家級外國文學刊物，時任大陸文化部部長的茅盾擔任首任主編。作為20世紀50-70年代中國大陸 唯一公開發行的專門譯介外國文學作品的期刊，它成為當時中國大陸人民瞭解、認識外國文學作品及文藝動態的最主要的管道之一。通過對這份期刊的研究，本文將1959年《譯文》更名為《世界文學》，這一現象置於1950年代中國大陸社會政治環境中，借助「翻譯即改寫」的理論視角，通過分析這份期刊當時更名的原因，以及《世界文學》如何參與了譯入語語境中翻譯文學經典的重構過程，深入探討當時中國文壇以及文學翻譯如何受到政治及時代社會因素所影響。Launched in July 1953 and discontinued on the eve of the Cultural Revolution in January 1966, Yi Wen, which literally means ＂Translated Literature,＂ was the only journal publishing translated foreign literature in Mainland China during the 1950s and the 1960s. It is meant to serve as one of the main platforms for the Chinese people to keep abreast of foreign literature and the latest literary trends in the world. During that time, China was dominated by Maoism and the unified communist ideology, and Mao Zedong's mandate that ＂literature should reflect politics＂ exerted ideological influences on the literary translation. As a state-sponsored journal run by the Chinese Writers Association, Yi Wen enjoyed a long-term high ＂political status.＂ In 1959, this journal changed its name from Yi Wen to Shijie Wenxue, which literally means World Literature. Up till now, in-depth case studies of the interactions between translation and politics since 1949 have been very limited and case studies of Yi Wen (World Literature) were especially so. According to André Lefevere, translation is a rewriting or manipulation of an original text and all rewritings reflect a certain ideology and poetics. Borrowing this concept from Lefevere, this essay examines the politics in translation in the People's Republic of China. Questions of concern are: why did the journal change its name from Yi Wen to Shijie Wenxue? How did the journal reveal the change in China's views of ＂the world＂ in 1959? How did this journal contribute to the (re)construction of a canon?